Gender Differences in the Outcomes of Computer-Assisted Language Instructional Strategies in Essay Writing: Case of Senior Secondary Classes in Ilorin City, Nigeria - Olatunji, Samson Olusola; Olaniran Kolawole, Clement Olusegun (Papers in Education and Development, 2022)
The study was conducted to determine what contribution gender could make to Nigerian students ' disposition to and performance in essay writing when exposed to computer-assisted language instructional strategies. Three senior secondary classes were selected in Ilorin, Kwara State. The pretestposttest control group quasi-experimental design was employed. Each class was assigned to an instructional strategy (collaborative computerassisted language instruction, autonomous computer-assisted language instruction, and conventional instruction respectively). The treatment to the groups lasted eight weeks. Computations of means and standard deviation as well as analysis of covariance were used in analyzing the data obtained. The findings showed that gender had significant effect on the students ' disposition to and significant effect on the students ' achievement in computer-assisted essay writing. Keywords: gender, gender achievement, language instruction strategies